Comparison of subglottic vs. non-subglottic secretion drainage in prevention of Ventilator Associated Pneumonia: A systematic review and meta-analysis. (April 2022) - Sanaie, Sarvin; Rahnemayan, Sama; Azizi, Saeed; Saghaleini, Seyed Hadi; Ghamari, Ali Akbar; Ghojazadeh, Morteza; Mahmoodpoor, Ata
Abstract: Introduction: Ventilator associated pneumonia is one of the most common nosocomial infections with a high mortality rate. Subglottic secretion drainage (SSD) has been studied extensively as a strategy for VAP prevention and several guidelines recommend its use. However, the use of SSD is not widespread, probably due to the weakness of the quality of evidence. Methods: A comprehensive search was performed through the online studies of PubMed, Scopus, and Cochrane Library using specific search terms. Included studies were randomized controlled trials that evaluated the effect of SSD on the incidence of VAP in critically ill patients under mechanical ventilation. Results: 28 clinical trials were included in this systematic review. Results showed a low heterogeneity among the studies (I 2  = 0%, p = 0.54). The forest plot showed that the incidence of VAP in SSD was significantly lower than Non-SSD (RR = 0.61; 95% CI, 0.54–0.68; P < 0.001). The Funnel plot results indicates no diffusion bias. Conclusion: The results of this meta-analysis showed that SSD significantly reduced the incidence of VAP. However, because of relatively small sample sizes and high risk of bias, we need more future trials to recommend the SSD as a routine daily practice in critically ill patients under mechanical ventilation.